Factors Affecting Purchase Intention towards Smartphone Brand: A Study on Bangladeshi Private University Students - Hossain, Md. Azmol; Islam, Zahidul; Islam, Sardar Mohammad Tauhidul; Mustafi, Mohitul Ameen Ahmed (Global Disclosure of Economics and Business, 2017)
In today’s technology based world, people are depending more and more on various technology devices. Smartphone is one of the most important devices people use mainly for communicating with others and some specific purposes. It is not an easy task to choose the right Smartphone for an individual’s needs when there are so many Smartphone brand available in the market. There are some critical factors affecting the individuals Smartphone purchase intention. This study aims to explore the factors that affect the purchase intention towards Smartphone brand. A structured questionnaire on 5-points Likert sclae was developed to collect data from 302 respondents who are studying in different private universities of Dhaka city in Bangladesh using convenient sampling method. Structural equation modeling was used to identify the significant factors affecting purchase intention towards Smartphone brand. Data was analyzed by using SmartPLS software. This study found that Price, Peer Influence and Product features are the factors highly significantly affect the purchase intention towards Smartphone Brand but not Brand Image. The findings of this research may help not only the private university students but also other consumers who intend to purchase Smartphone. Smartphone manufacturer also consider these factors for Bangladeshi market.